Hubungan Kelekatan Orang Tua Dengan Anak Usia Dini Terhadap Adiksi Gadget di Paud Intan Desa Asembagus Kraksaan - Evi Silviana; Yessy Nur; Tutik Ekasari (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Gadgets greatly impact the pattern of human life both in terms of mindset, taste patterns and behavior patterns. The use of gadgets in everyday life does not only have an impact on the thoughts, feelings and behavior of adults, but children are also not spared from its impact. Child attachment early in life can be directed at someone who has nothing to do with child rearing, but it can happen tosomeone the child chooses as the object of attachment. The purpose of this study was to find out whether there is a correlation between people's attachment to early childhood gadget addiction at Early Childhood Education. This research is a descriptive research. Total population of 30 people. A sample of 30 people was taken by total sampling technique. The research instruments used were the IPPA questionnaire and the smartphone addiction test questionnaire for mobile motoring. Bivariate analysis using the Chi Square Statistical Test. The results showed that the respondents had high attachment to their parents, namely 16 children (53.3%), moderate attachment of 7 children (23.3%), and low attachment of 7 children (23.3%). From the results of the smartphone addiction test questionnaire for mobile motoring, it was found that 15 children (50.0%) were not dependent on gadgets, 4 children had mild dependence (13.3%), 3 children were moderately addicted (10.0), and 8 children were addicted. (26.7%). Based on the Chi Square test, it is known that the P Value is 0.004 with α 0.05. Because the significance value is < α, H0 is rejected and H1 is accepted, which means that there is a correlation between parents and early childhood attachment to gadget addiction at PAUD Intan, Asembagus village kraksaan. It is hoped that the results of this research can be used as input for parents regarding the importance of accompanying children so that children do not experience gadget addiction.